Challenges and drivers of BIM implementation in Sarawak Construction Industry - Peniel, Ang Soon Ern; Ali, Nur Aida; Tsai, Kai Len; Kasim, Narimah; Ali, Roslinda (2024)
Building Information Modelling (BIM) is a process established to enhance the construction project efficiency. It has been used in Malaysia and globally especially in the construction sectors. There has been a gradual acceptance of Malaysia construction industry stakeholders especially in the Peninsular in the uptake of BIM implementation. However, in Sarawak itself, this point turns out to be much more burdensome as the development projects in the state turns out to be more branched out and complex. Research shows on BIM uptake in Sarawak and Sabah lagging at a low 6% as compared to Peninsular of 78% in the central region only. Thus, this research objectives are to investigate the challenges faced by industry stakeholders in implementing BIM and also to explore on the drivers that increases the usage of BIM Sarawak construction industry. The virtual semi-structured interview sessions target the policy makers such as Public Works Department (JKR) and contractors from G6 to G7 in Kuching, Sarawak. The data obtained will be analysed using a qualitative content analysis technique supported by matrix table method. The challenges to BIM implementation are lack of readiness in BIM implementation, lack of manpower and special equipment’s for BIM and lastly, BIM training, courses and software are costly. The driving factors of the BIM implementations are to improve organizations collaboration, to boost and enhance company capability in technology and mandatory rule imposed by the government to implement BIM. This research is significant to spearhead initiatives by tackling the challenges and generate better driving factors for BIM implementations especially in Sarawak construction industry